The donor of carbon monoxide (CORM-2) affects the level of serum immunoglobulins and the state of the bone marrow during the immune response in mice - S. P. Beschasnyi; O. M. Hasiuk (Zaporozhye State Medical University, 2020)
Toxic carbon monoxide in small concentrations has pro-apoptotic, anti-allergic, vasodilator effects, and stimulates angiogenesis. The problem with the therapeutic use of low doses of carbon monoxide is that it is difficult to dose. To control the amount and gradual release of carbon monoxide, non-toxic preparation is used - CO donor based on carbonyl compound of ruthenium (CORM-2). The aim - is to identify the effect of CORM-2 on the level of immunoglobulins in the blood serum and bone marrow of mice under conditions of inducing an immune response. Materials and methods. 3 groups of 15 white laboratory mice each were formed. Induction of the immune response was due to the intraperitoneal administration of xenogenic red blood cells. The first experimental group on the first day of immunization received CORM-2 (20 mg/kg), group No. 2 - on the 5th day after immunization (period of the productive phase). The control group consisted of immunized animals that did not receive CORM-2. The amount of IgA, IgM, and IgG in blood serum was determined by ELISA on the 2nd and 6th day after immunization. At the end of the experiment, bone marrow cell populations were counted. Results. After the injection of CORM-2 during the induction phase of the immune response, it inhibits the production of immunoglobulins. In comparison with the control, the level of IgA and IgG is reduced, but the amount of IgM remains unchanged. In the bone marrow, the number of monocytes, erythroblasts, and normoblasts, as well as lymphoblasts and plasma cells, increased. At the same time, the number of myeloblasts, myelocytes, basophilic normoblasts, and megakaryocytes decreased. The use of CORM-2 during the productive phase caused a decrease in the level of IgM and IgG with a simultaneous increase in the level of IgA. The number of neutrophils, eosinophils, monocytes, polychromophilic and oxyphilic normoblasts, lymphocytes, and plasma cells in the bone marrow increased. However, the number of myeloblasts, promyelocytes, myelocytes, metamyelocytes, basophilic normoblasts, and megakaryocytes decreased. Conclusions. The impact of the CORM-2 on the inductive phase of the immune response leads to inhibition of the production of immunoglobulins. The injection of CORM-2 during the productive phase of the immune response decreased the level of IgM and IgG, but at the same time, an increase in the level of IgA was observed. After the injection of CORM-2, in the bone marrow, the number of monocytes, lymphocytes, and plasma cells increased. The results indicate that CORM-2 is able to modulate the immune response.